Comparison of Sex Differences in Outcomes of Patients With Aneurysmal Subarachnoid Hemorrhage: A Single-Center Retrospective Study - Cai, Yuankun; Liu, Zheng; Jia, Chenguang; Zhao, Jingwei; Chai, Songshan; Li, Zhengwei; Xu, Chengshi; Zhang, Tingbao; Ma, Yihui; Ma, Chao; Chen, Xinjun; Jiang, Pucha; et al. (Frontiers in Neurology, 2022)
Background Sex differences in the outcomes of patients with aneurysmal subarachnoid hemorrhage (aSAH) remain controversial. The aim of this study was to evaluate sex differences in the outcomes of patients with aSAH. Method This study retrospectively analyzed the clinical data of consecutive patients with aSAH, admitted to the Department of Neurosurgery, Wuhan University Zhongnan Hospital, from May 1, 2020 to December 31, 2020. The modified Rankin Scale (mRS) score was used to evaluate the prognosis of patients at discharge. Outcome indicators included cerebral ischemia, hydrocephalus, and mRS ≥ 2 at discharge. Results The majority (65%) of the 287 patients with aSAH included in the study were females. Patients were divided into female (n = 184) and male (n = 99) groups; the female patients were significantly older than the male patients (61.3 ± 8.5 years vs. 60.0 ± 8.5 years, p = 0.032). The incidence of comorbidities (hypertension, diabetes, and heart disease) was higher in the female group than in the male group, but the difference was not statistically significant. Although more female patients than male patients underwent endovascular treatment, there was no statistical difference in the treatment approach between the two groups. Comparison of post-operative complications and mRS scores at discharge revealed that the rate of cerebral ischemia and mRS ≥ 2 at discharge were significantly higher among female patients than among male patients. Moreover, this difference persisted after propensity adjustment for age and treatment approach. Analysis of risk factors for poor prognosis at discharge in both pre- and post-adjustment patients revealed cerebral ischemia and high mFisher score (mFisher = 3/4) to be independent risk factors. Conclusion Female patients with aSAH have a worse prognosis than male patients, and this difference may be because women are more susceptible to cerebral ischemia.